Participatory rangeland management learning kit - Ng'ang'a, Irene N. (International Livestock Research Institute, 2022)
A learning toolkit for Participatory rangeland management (PRM) used to facilitate a community-owned and participatory process for planning and implementation of sustainable resource management for rangelands. The toolkit was developed by ILRI